Peripheral immune factors are elevated in women with current or recent alcohol dependence and associated with altered mood and memory. (1st July 2017) - Wilhelm, Clare J.; Fuller, Bret E.; Huckans, Marilyn; Loftis, Jennifer M.
Graphical abstract: Highlights: Affective symptoms and memory problems are increased in alcohol dependent men and women. Increases in tissue inhibitor of metalloproteinase 1 (TIMP-1) and brain derived neurotrophic factor (BDNF) are associated with alcohol dependence, but only in women. TIMP-1 correlates with depression, anxiety, and memory complaints in women. Abstract: Background: The adverse effects of alcohol on brain function result, in part, from inflammatory processes. The sex-specific neuropsychiatric consequences and inflammatory status of active alcohol dependence and early remission from dependence have not been investigated. Methods: Neuropsychiatric symptoms, inflammatory factors, and liver enzymes were compared in a prospective cohort study of adults with (n = 51) or without (n = 31) a current or recent history of alcohol dependence. Results: Neuropsychiatric profiles were similar in adults with current or recent alcohol dependence regardless of sex. In male and female participants measures of depression (female p < 0.05, male p < 0.001), anxiety (female p < 0.001, male p < 0.001), and memory complaints (female p < 0.001, male p < 0.05) were elevated, relative to non-dependent controls. Significant sex × alcohol dependence history interactions were observed for plasma levels of tissue inhibitor of metalloproteinase 1 (TIMP-1) and brain derived neurotrophic factor (BDNF), with women in the alcohol dependent group exhibiting increased levels of both analytes (p < 0.05) relative to controls. Positive correlations between TIMP-1 levels and measures of depression (r 2  = 0.35, p < 0.01), anxiety (r 2  = 0.24, p < 0.05) and memory complaints (r 2  = 0.44, p < 0.01) were found in female, but not male, participants. Conclusions: Though neuropsychiatric profiles were similar for men and women with current or recent alcohol dependence, plasma factors associated with increases in depression, anxiety, and memory impairment differed and support the need to tailor treatments based on sex.